Peramalan Persediaan Barang Menggunakan Metode Weighted Moving Average dan Metode Double Exponential Smoothing - Muh Latif; Rengga Herdiansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The management of goods inventory at PT EDS Manufacturing Indonesia (PEMI) is still manual, on the other hand there is no policy that regulates what methods can be used to forecast the inventory of goods and also the absence of an estimate of the number of goods that will be purchased by customers so that the number of goods, inventory is often mistaken and causes a buildup of goods in the warehouse. For that, a method is needed that can be systemized according to sales data in the forecasting of goods inventory. There are several methods that can be implemented including Weight Moving Average and Double Exponential Smoothing. The Weight Moving Average method is a method that gives different weights to each historical while the Double Exponential Smoothing method is a method that has a smoothing value twice at the time before the actual data. The data used in this study is quarterly before the forecasting. This thesis aims to design and build a web-based application using the Weight Moving Average and Double Exponential Smoothing methods, the results of the two methods compared to find out which forecasting results have the smallest error value, where the smallest error value can be referenced for the upcoming inventory of goods